2020
DOI: 10.1080/15592324.2020.1764184
|View full text |Cite
|
Sign up to set email alerts
|

Subject: UV-B radiation and low temperature promoted hypericin biosynthesis in adventitious root culture of Hypericum perforatum

Abstract: The hypericin is assumed as a highly demanded and key bioactive compound, which has antiviral, antimicrobial, antioxidant, and antitumor properties isolated from Hypericum perforatum. Nowadays, increasing bioactive molecules' contents through generating novel compounds is one of the major research objectives of H. perforatum biotechnology; however, this plant remains recalcitrant and unmanageable to Agrobacterium mediated transformation and genetic improvement programs. In order to overcome these challenges, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…While low temperatures improving the plant growth and Hyp accumulation by stimulating related gene expressions has been observed in H. perforatum [20,22,27,28], the mechanism responsible for temperature-dependent growth and Hyp biosynthesis has not been dissected. Here, it is shown that there is a greater plant biomass and Hyp accumulation, more leaf dark glands, stomatal density and rounded stomatal shape at 15 compared to 22 • C. By treating seedlings at 15 and 22 • C, ca.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While low temperatures improving the plant growth and Hyp accumulation by stimulating related gene expressions has been observed in H. perforatum [20,22,27,28], the mechanism responsible for temperature-dependent growth and Hyp biosynthesis has not been dissected. Here, it is shown that there is a greater plant biomass and Hyp accumulation, more leaf dark glands, stomatal density and rounded stomatal shape at 15 compared to 22 • C. By treating seedlings at 15 and 22 • C, ca.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence shows that H. perforatum plants can adapt to low temperatures by increasing the biomass and morphogenesis (e.g., leaf area, number of stem and its internode and root), and low temperatures can improve Hyp biosynthesis by increasing the number of dark glands and related gene expressions [10,12,20,22,27,28]. The current study exhibited greater biomass by increasing the stomatal density and opening percentages, as well as a more rounded stomatal shape with the ratio of length/width and greater Hyp content via the overexpression of 61 genes involved in Hyp biosynthesis (Figures 2 and 3 and Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations